2000
DOI: 10.23986/afsci.5644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding level and diet type on the performance of crossbred suckler cows and their calves

Abstract: A 2´2 factorial design experiment with 32 spring-calving Hereford-Ayrshire and 31 Limousine-Ayrshire suckler cows was conducted to compare the effects of diets based on hay (H) or urea-treated straw (US) at two feeding levels (moderate; M and low; L) on the performance of cows and their calves. For feeding level L, the amount of feed was restricted to 70% of that for feeding level M. Diet H was based on hay while for the US-diet, hay was replaced by urea-treated straw and barley (M:1.1 and L:0.8 kg dry matter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
2
8
1
Order By: Relevance
“…Condition at calving was obviously suitable for this stage of production for mature, crossbred cows, but inspite of this, cows on the diet 1 lost almost double the LW relative to those fed diet 2, but compensated for such losses on pasture. These results are in accordance with earlier results under Finnish conditions with similar non-mature cows (Manninen et al 2000). Hodgson et al (1980) offered spring-calving Hereford-Friesian and Blue-Grey cows hay and concentrate from calving until turnout sufficient for maintenance and either 2.3 or 9.0 kg milk/d and observed that cows on the lower level of feeding lost more LW (1730 vs. 1260 g/d), losses which are consistent with values observed in the current study.…”
Section: Manninen M and Huhta H Effects Of Feeding Levels On Perforsupporting
confidence: 94%
See 3 more Smart Citations
“…Condition at calving was obviously suitable for this stage of production for mature, crossbred cows, but inspite of this, cows on the diet 1 lost almost double the LW relative to those fed diet 2, but compensated for such losses on pasture. These results are in accordance with earlier results under Finnish conditions with similar non-mature cows (Manninen et al 2000). Hodgson et al (1980) offered spring-calving Hereford-Friesian and Blue-Grey cows hay and concentrate from calving until turnout sufficient for maintenance and either 2.3 or 9.0 kg milk/d and observed that cows on the lower level of feeding lost more LW (1730 vs. 1260 g/d), losses which are consistent with values observed in the current study.…”
Section: Manninen M and Huhta H Effects Of Feeding Levels On Perforsupporting
confidence: 94%
“…A low level of feeding in marginal climatic areas did not affect cow or calf health but depressed reproductive performance (Manninen et al 2000). However, cows replenished live weight losses during the grazing period on sufficiently good quality pasture.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Indoor feeding of beef cows is usually based on inexpensive, low-energy feeds such as straw, treated straw (Mann et al 1988, Fike et al 1995, Manninen et al 2000 or straw with protein or energy supplements (Alawa et al 1986, Alawa et al 1987, Alawa et al 1988, Beck et al 1992). Good quality grass silage is not used for beef cows ad libitum due to its high energy content, especially for cows in good body condition score pre-calving.…”
Section: Introductionmentioning
confidence: 99%